ANALYSIS OF STOCK PRICE MOVEMENTS ON THE JAKARTA ISLAMIC INDEX DURING THE COVID-19 PANDEMIC - Kholid, Mochammad; Nofal, Mohammad; Hatma, Ramli (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
The Covid-19 pandemic has caused panic among capital market participants, which led to stock selling in the market and resulted in a very significant decline in the stock price of the Jakarta Islamic Index (JII) and all sectoral indices on the Indonesia Stock Exchange. This research aims to analyze the movement of the Jakarta Islamic Index and its sectoral indices as well during the Covid-19 pandemic from January to December 2020. The JII sectoral index is not yet available, so it is calculated using a sample of 20 sharia stocks, from 38 stock populations in JII, selected based on the purposive sampling method. This research type is an event study using the moving average (MA) method with descriptive analysis techniques. The results indicate that JII movement pattern tends to fluctuate during 2020. The decline in JII began to be seen in February and March. It experienced a very significant peak of decrease. The events of the government's first announcement of the Covid-19 case in early March continued to trigger the drop of JII. In the second week of March, WHO announced Covid-19 as a Pandemic adding to JII's decline to its lowest position throughout 2020. The Property, Infrastructure, and Miscellaneous Industries sectors were most affected by Covid-19 events in 2020, and these sectors experienced the most profound decline during 2020. Keywords: Covid-19 Pandemic, JII, and Shari’ah Stock Price